EDUKASI PENCEGAHAN DEMAM BERDARAH DENGUE MELALUI POLA HIDUP SEHAT DAN BERSIH DI DESA LIPRAK KIDUL banyuanyar probolinggo - Pratiwi, Ari Dwi; Dewanty, Megananda Aruna; Fatmasari, Eka Putri; Khoiriyah, Nur ‘Azizatul; Fadel, Achmad Ghulam; Mugiyati, Mugiyati (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. This disease poses a serious threat in tropical regions, including Indonesia. Probolinggo Regency, East Java, experienced a significant increase in DHF cases in 2023-2024, with 315 cases and 18 deaths in several sub-districts. The unkempt environment in Liprak Kidul Village is a major factor in the proliferation of Aedes aegypti mosquitoes. This study aims to educate the community of Liprak Kidul Village on the prevention of DHF through healthy and clean-living habits. The method used is Participatory Action Research (PAR) with steps including problem identification, action planning, implementation, distribution of medication, and follow-up. The results of the study indicate that clean village through community service program, education and practice of hand washing, waste management using the 5R concept (Reuse, Reduce, Recycle, Replace, and Replant), as well as education on healthy toilets and the provision of abate powder successfully increased community awareness of the importance of environmental cleanliness and health. However, challenges such as limited resources and lack of community awareness still need to be addressed to achieve long-term success in DHF prevention in Liprak Kidul Village.